On writing - Bukowski, Charles (Ecco, an imprint of HarperCollinsPublishers, 2015)
"Charles Bukowski's stories, poems, and novels have left an enduring mark on our culture. In this collection of correspondence--letters to publishers, editors, friends, and fellow writers--the writer shares his insights on the art of creation." --